2021
DOI: 10.1101/2021.02.28.21252383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trajectories of Clinical and Laboratory Characteristics Associated with COVID-19 in Hemodialysis Patients by Survival

Abstract: Introduction: The clinical impact of COVID-19 has not been established in the dialysis population. We evaluated the trajectories of clinical and laboratory parameters in hemodialysis (HD) patients. Methods: We used data from adult HD patients treated at an integrated kidney disease company who received a RT-PCR test to investigate suspicion of a SARS-CoV-2 infection between 01 May and 01 Sep 2020. Nonparametric smoothing splines were used to fit data for individual trajectories and estimate the mean change ove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The selection process is illustrated in Figure 1. The 22 included studies 1637 were from 17 countries, with a total of 13,191 patients. Meta-analysis of epidemiological, clinical, and radiological data from COVID-19 patients undergoing MHD are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection process is illustrated in Figure 1. The 22 included studies 1637 were from 17 countries, with a total of 13,191 patients. Meta-analysis of epidemiological, clinical, and radiological data from COVID-19 patients undergoing MHD are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, the world has witnessed an increasing number of such cases. 1 Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the putative causative agent of coronavirus disease 2019 (COVID- 19), resulted in this pneumonia. Analysis of the SARS-CoV-2 genome has shown that it is phylogenetically close to SARS-CoV.…”
Section: Introductionmentioning
confidence: 99%
“…1). These timepoints were selected based off expert knowledge in the domain of medicine and physiology and a prior investigation that estimated the timing of physiological disturbances during the onset of COVID-19 [18].…”
Section: Independent Variablesmentioning
confidence: 99%
“…A past work identified disturbances in physiology start about 14 days before COVID-19, with the most meaningful changes in clinical and laboratory values being seen at presentation with the first signs and symptoms of the disease [18]. Therefore, the most recent value within 14 days of COVID-19 was chosen to provide a representation of the patient's clinical status at presentation with signs of symptoms that led to identification of COVID-19.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation